2020
DOI: 10.3390/jcm9082419
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-199b Deregulation Shows a Strong SET-Independent Prognostic Value in Early-Stage Colorectal Cancer

Abstract: The endogenous PP2A inhibitor SET Nuclear Proto-Oncogene (SET) has been reported to play oncogenic roles and determines poor outcomes in colorectal cancer (CRC). Our group previously showed that miR-199b is deregulated in metastatic CRC, and reduced the cell viability and enhanced the sensitivity of CRC cells to standard induction chemotherapy drugs, mainly through direct negative SET regulation. Clinically, miR-199b downregulation was identified as the molecular mechanism responsible for SET overexpression in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…However, other studies in the literature have demonstrated that miR-199b increases 5-FU sensitivity of CRC cells through the regulation of the SIRT1/CREB/KISS1 as well as DDR1/JAG 1 signaling pathways [ 27 , 28 ]. Therefore, these observations could explain that this alteration serves as a marker of poor outcome in CRC independently of SET [ 30 ], and are in concordance with our results showed here about the clinical impact of miR-199b as a predictor of pathological response to neoadjuvant CRT in LARC patients.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…However, other studies in the literature have demonstrated that miR-199b increases 5-FU sensitivity of CRC cells through the regulation of the SIRT1/CREB/KISS1 as well as DDR1/JAG 1 signaling pathways [ 27 , 28 ]. Therefore, these observations could explain that this alteration serves as a marker of poor outcome in CRC independently of SET [ 30 ], and are in concordance with our results showed here about the clinical impact of miR-199b as a predictor of pathological response to neoadjuvant CRT in LARC patients.…”
Section: Discussionsupporting
confidence: 92%
“…These results would suggest that there are no differences in the clinical impact of LARC patients by age. Therefore, the differences previously described in early stage CRC [ 30 ] could be higher in the subgroup of colon cancer compared to rectal cancer patients. This issue needs to be clarified in forthcoming studies with series including colon and rectal cancer patients and analyses of them separately.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations